(untitled) (Pesquisa Odontológica Brasileira, 2000)
The aim of this study was to compare four systems of titanium plates and screws (diameter of 2.0 mm) used for internal rigid fixation. From them, two were made in Brazil (Engimplan and Bucomax), one in Switzerland (Synthes), and the other, in Germany (W. Lorenz). The following analyses were done: chemical analysis using Energy Dispersive Spectroscopy (EDS) and Atomic Emission Spectroscopy (AES), measurement of dimensions and bending resistance test. The obtained results allow to conclude that both Brazilian systems showed inferior behavior regarding dimensional standards. The bending assay showed that the Brazilian systems are similar to each other. However, the W. Lorenz screws are made of titanium-6aluminum-4vanadium alloy, which can be the reason for their better performance in the bending assay, when compared with that of the other three systems. The remaining plates and screws are made of commercially pure titanium as confirmed by EDS and AES.